2012
DOI: 10.1002/jclp.21887
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Diagnostic Efficiency of Post‐Deployment Mental Health Screens

Abstract: The PDHRA MDD, PTSD, and alcohol abuse screens appear to be functioning well in accurately ruling out these diagnoses, consistent with a population-level screening program. Cross validation of the current results is indicated. Additional refinement may yield more sensitive screening measures within constraints imposed by the low base rates in a typically healthy population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…2,[11][12][13] Further, Freedy and his colleagues found that the PC-PTSD performed similarly to the PTSD Checklist -Civilian version (PCL-C) 2 , a wellestablished longer measure of PTSD that assesses the full range of symptoms. 14,15 Because the PC-PTSD has demonstrated excellent diagnostic accuracy and clinical utility with various groups of primary care patients, 2,9,16,17 it is mandated for use in VA and DoD settings. 18,19 In 2013, the fifth edition of the Diagnostic and Statistical Manual (DSM-5) 20 introduced significant revisions to the PTSD diagnosis based on research suggesting that these changes better reflect the PTSD latent construct.…”
Section: T He Prevalence Of Posttraumatic Stress Disorder (Ptsd) Inmentioning
confidence: 99%
“…2,[11][12][13] Further, Freedy and his colleagues found that the PC-PTSD performed similarly to the PTSD Checklist -Civilian version (PCL-C) 2 , a wellestablished longer measure of PTSD that assesses the full range of symptoms. 14,15 Because the PC-PTSD has demonstrated excellent diagnostic accuracy and clinical utility with various groups of primary care patients, 2,9,16,17 it is mandated for use in VA and DoD settings. 18,19 In 2013, the fifth edition of the Diagnostic and Statistical Manual (DSM-5) 20 introduced significant revisions to the PTSD diagnosis based on research suggesting that these changes better reflect the PTSD latent construct.…”
Section: T He Prevalence Of Posttraumatic Stress Disorder (Ptsd) Inmentioning
confidence: 99%
“…A growing number of risk factors for suicide ideation and suicide attempts have been confirmed among military personnel and veterans, with results largely supporting the notion that risk factors for suicide ideation and suicide attempts are the same for military personnel and veterans as they are for nonmilitary samples. For example, numerous studies have identified many psychiatric conditions such as posttraumatic stress disorder (PTSD), depression, and substance use disorders to be risk factors for suicide ideation and suicide attempts among military personnel and veterans (Bryan, Clemans, & Hernandez, 2012; Ilgen et al, 2012; LeardMann et al, 2013; Nock et al, 2014; Skopp et al, 2012), similar to findings in nonmilitary settings (Kessler et al, 1999).…”
mentioning
confidence: 90%
“…This 4-item measure, which is based on the PTSD diagnostic criteria in the Diagnostic and Statistical Manual of Mental Disorders (Fourth Edition), 23 has excellent psychometric properties. 22,[24][25][26] In 2013, the American Psychiatric Association presented revised PTSD diagnostic criteria in the Diagnostic and Statistical Manual of Mental Disorders (Fifth Edition) (DSM-5). 27 The PC-PTSD was revised as the PC-PTSD-5 to reflect DSM-5 criteria.…”
Section: Introductionmentioning
confidence: 99%
“…VA uses the Primary Care PTSD Screen (PC-PTSD) for screening. This 4-item measure, which is based on the PTSD diagnostic criteria in the Diagnostic and Statistical Manual of Mental Disorders (Fourth Edition), has excellent psychometric properties …”
Section: Introductionmentioning
confidence: 99%